Financial Sector Assessment : Senegal - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) is based on the work of the joint International Monetary Fund (IMF)/World Bank mission that visited Senegal as part of the Financial Sector Assessment Program (FSAP) from November 6-17, 2000 and January 28-February 5, 200l . Members of the team also visited Cote d'Ivoire in order to conduct assessments of the regional capital market, securities commission, and banking commission, and Lome, Togo for discussions with the regional social security regulator, CIPRES. The FSAP mission's findings were discussed with the authorities in July 2001 in the context of the 2001 article four consultation. This report summarizes the main findings of the mission, identifies key financial sector vulnerabilities, and provides policy recommendations.